POLITICS OF CHANGE IN MIDDLE EAST AND NORTH AFRICA SINCE ARAB SPRING ([S.l.])
1 online resource
Keywords: A decade since the eruption of Arab Spring protests in the Middle East and North Africa, the region continues to confront the primary causes of the popular disenchantment including economic deprivation, bad governance, corruption and limited avenues for political expression. Democratisation, the buzzword in 2011 has given way to debates around conflict management and resolution. Simultaneously, there are mounting economic challenges throughout the region that have been aggravated by the COVID-19 pandemic. But there are some silver linings such as a focus on reforms, greater scrutiny against corruption, demand for better governance, and awareness regarding women empowerment and rights of minorities. The volume, Politics of Change in the Middle East and North Africa since Arab Spring: A Lost Decade?, commemorates the ten years of the eruption of Arab Spring protests. It captures some of the prevailing political, economic, strategic and social issues in MENA through thematic or country-specific essays that explore the ongoing transformations and underline how despite the hopelessness, the MENA societies have made progress on various fronts. Print edition not for sale in South Asia (India, Sri Lanka, Nepal, Bangladesh, Pakistan and Bhutan).